Temporal association of acute hepatitis A and Plasmodium falciparum malaria in children - Klein Klouwenberg, Peter; Sasi, Philip; Bashraheil, Mahfudh; Awuondo, Ken; Bonten, Marc; Berkley, James; Marsh, Kevin; Borrmann, Steffen (PLOS ONE, 2011)
Background: In sub-Saharan Africa, Plasmodium falciparum and hepatitis A (HAV) infections are common, especially in children. Co-infections with these two pathogens may therefore occur, but it is unknown if temporal clustering exists. Materials and Methods We studied the pattern of co-infection of P. falciparum malaria and acute HAV in Kenyan children under the age of 5 years in a cohort of children presenting with uncomplicated P. falciparum malaria. HAV status was determined during a 3-month follow-up period. Discussion Among 222 cases of uncomplicated malaria, 10 patients were anti-HAV IgM positive. The incidence of HAV infections during P. falciparum malaria was 1.7 (95% CI 0.81-3.1) infections/person-year while the cumulative incidence of HAV over the 3-month follow-up period was 0.27 (95% CI 0.14-0.50) infections/person-year. Children with or without HAV co-infections had similar mean P. falciparum asexual parasite densities at presentation (31,000/µL vs. 34,000/µL, respectively), largely exceeding the pyrogenic threshold of 2,500 parasites/µL in this population and minimizing risk of over-diagnosis of malaria as an explanation. Conclusion The observed temporal association between acute HAV and P. falciparum malaria suggests that co-infections of these two hepatotrophic human pathogens may result from changes in host susceptibility. Testing this hypothesis will require larger prospective studies.